EPEN-31. SUBGROUP SPECIFIC LONG-TERM SURVIVAL AND NEUROCOGNITIVE OUTCOMES IN POSTERIOR FOSSA EPENDYMOMA (PFE). Issue 2 (22nd June 2018) - Zapotocky, Michal; Beera, Kiran; Adamski, Jenny; Guger, Sharon; Janzen, Laura; Laperierre, Normand; Bartels, Ute; Hawkins, Cynthia; Taylor, Michael; Bouffet, Eric; Mabbott, Donald; Ramaswamy, Vijay
Abstract: BACKGROUND: PFE comprises two groups, EPN_PFA and EPN_PFB with stark differences in outcome. However, the long-term outcomes of PFA ependymoma and the pattern of relapse have not been fully described. We aimed to identify predictors of survival and neurocognitive outcome in a large consecutive cohort of subgrouped PFE over three decades. RESULTS: Seventy-three PFE were identified, of which 89% were PFA. There were no relapses amongst PFB. Ten-year PFS of PFA was poor at 37 +/- 7%. Analysis of consecutive 10-year epochs revealed significant improvement in PFS/OS over time (2005–2014 compared to 1985–1994 and 1995–2004). This pertains to the GTR rate increased from 35% to 77% and use of upfront radiation increased from 65% to 96% over the observed period and confirmed in a multivariable model. The pattern of relapse changed over time, related to GTR PFA relapsing with metastasis. Analysis of longitudinal neuropsychological outcomes in a mixed linear model shows continuous declines in IQ over time with upfront conformal radiation, which are particularly pronounced in infants under the age of 3 (FSIQ -1.33 points/year). CONCLUSIONS: Data from a molecularly informed large prospective cohort of PFE clearly indicate improved survival over time, related to more aggressive surgery and upfront radiation. However for the first time in a subgrouped cohort, we show that this approach results in reduced neurocognitive outcomes over time. Our data suggest that all children with EPN_PFA should receive upfront radiation and be concomitantly prioritized for early neuropsychological testing and intervention.